(untitled) (Acta Polytechnica CTU Proceedings, 2015)
Cataclysmic variables emit over a wide range of the electromagnetic spectrum. In this paper I will review observations of polars in relevant passbands obtained during the last decade and will discuss their diagnostical potential to access the physics of the main components within the binary systems. This will include a discussion of intrinsic source variability and the quest for simultaneous multi-frequency observations.